1994
DOI: 10.1136/bmj.309.6963.1189
|View full text |Cite
|
Sign up to set email alerts
|

Environmental lead and children's intelligence: a systematic review of the epidemiological evidence

Abstract: While low level lead exposure may cause a small IQ deficit, other explanations need considering: are the published studies representative; is there inadequate allowance for confounders; are there selection biases in recruiting and following children; and do children of lower IQ adopt behaviour which makes them more prone to lead uptake (reverse causality)? Even if moderate increases in body lead burden adversely affect IQ, a threshold below which there is negligible influence cannot currently be determined. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
2
15

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(236 citation statements)
references
References 26 publications
5
214
2
15
Order By: Relevance
“…The strength of this association and its time course have been observed to be similar in multiple studies in several countries. 23 In most countries, including the United States, blood lead concentrations peak at approximately 2 years of age and then decrease without intervention. Blood lead concentration is associated with lower IQ scores as IQ becomes testable reliably, which is at approximately 5 years of age.…”
Section: Subclinical Effectsmentioning
confidence: 99%
“…The strength of this association and its time course have been observed to be similar in multiple studies in several countries. 23 In most countries, including the United States, blood lead concentrations peak at approximately 2 years of age and then decrease without intervention. Blood lead concentration is associated with lower IQ scores as IQ becomes testable reliably, which is at approximately 5 years of age.…”
Section: Subclinical Effectsmentioning
confidence: 99%
“…By the end of 2002, the majority of human data indicated that there were persistent and deleterious effects of BPb levels above 10 µg/dl on children's brain function, including lowered intelligence, behavioral problems and diminished school performance [76][77][78][79][80][81][82][83] ; whereas, German researchers, who evaluated 24 selected publications in a meta-analysis 84,85) , concluded that neurobehavioral deficits due to lead exposure in adults were associated with average BPb levels between 37 and 52 µg/dl. Thereafter, Canfield et al reported that BPb levels, even those below 10 µg/dl, were inversely associated with children's intelligence quotient (IQ) scores at 3 and 5 yr of age, and that associated declines in IQ were greater at these levels than at higher levels 4) .…”
Section: Recent Perspective On Lead Toxicity In Childrenmentioning
confidence: 99%
“…A number of epidemiologic studies done since the 1980s have revealed that Pb impairs normal development of cognitive functions of children [1]. Exposure to Pb has been related to lower intelligence quotient (IQ) [2], poor academic achievement [3], and delinquent behavior [4]. Moreover, concern has recently been raised that adverse effects are seen at exposure levels lower than were considered safe in the past [5,6].…”
Section: Introductionmentioning
confidence: 99%